2015
DOI: 10.1155/2015/849472
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Obstructive Sleep Apnea and Parkinson’s Disease: Possible Mechanisms and Implications for Cognitive Function

Abstract: Parkinson's disease (PD) is a relentlessly progressive neurodegenerative disorder associated with hallmark motor and nonmotor symptoms (NMS) such as sleep disturbances and cognitive dysfunction. While dopaminergic treatments have improved the motor aspects of PD, progression remains inevitable. Research has recently increasingly focused on strategies to modify disease progression and on nonmotor manifestations of PD, given their impact on patients' quality of life. Obstructive sleep apnea (OSA) is a treatable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 151 publications
2
34
0
1
Order By: Relevance
“…[ 20 21 22 ] OSA has a relatively high prevalence among patients with neurodegenerative diseases. [ 14 18 19 ] Many studies report down-regulation of Wnt signaling in the pathogenesis of PD, and also highlight the importance of this pathway in neuroprotection. [ 20 ] Godin et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 21 22 ] OSA has a relatively high prevalence among patients with neurodegenerative diseases. [ 14 18 19 ] Many studies report down-regulation of Wnt signaling in the pathogenesis of PD, and also highlight the importance of this pathway in neuroprotection. [ 20 ] Godin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Kaminska et al . [ 14 ] reported that sleep disturbances were frequent in Parkinson's disease (PD). These include insomnia, hypersomnia, sleep architecture, and circadian abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep apnea may have central, obstructive/peripheral or mixed causes. It has been hypothesized that sleep apneainduced chronic intermittent hypoxia may increase oxidative stress and inflammation [33], which may contribute to the pathophysiology of PD [34]. A recent 3-year nationwide retrospective populationbased study of 1,944 Taiwanese patients with sleep apnea and 9,720 matched control subjects showed a higher risk of incident PD diagnosis (0.9%) in the apneic patients compared to 0.4% in the controls [35].…”
Section: Sleep Apnea and Incident Pd: Intermittent Hypo-oxygenation Amentioning
confidence: 99%
“…Recently, De Natale et al [120] showed that abnormalities in brainstem reflexes (vestibular-evoked myogenic potential) were more severe in patients with advanced Parkinson's disease compared with patients in the early phase and were significantly correlated with high scores on RBD Screening Questionnaire, an indicator for RBD severity. Similarly, dysfunction in brainstem ventilatory control mechanisms may be the link for the involvement of Parkinson's disease in the pathogenesis of SDB [93,94]. …”
Section: Sleep-wake Neurobiology In Prodromal Parkinson's Diseasementioning
confidence: 99%